Tourists' Intention to Visit Royal Cemetery as a Dark Tourism Destination: The Role of Destination Image, Self-Congruence, and Destination Personality - Suhud, Usep; Allan, Mamoon; Hoo, Wong Chee; Azinuddin, Muaz; Wolor, Christian Wiradendi (Journal of Ecohumanism, 2024)
This study seeks to investigate the effect of destination image, self-congruence, and destination personality on the visitors' intentions to visit the Imogiri Royal Cemetery, Yogyakarta Special Region, Indonesia. The cemetery is considered a historical and cultural place wherein a few kings and sultans who once ruled Java lie buried. Thousands of tourists visit this place throughout the year, especially on dates that have great significance in the Islamic and Javanese calendars. Data were collected from a convenience sample comprising of 220 tourists in Yogyakarta. Results show that destination image is an antecedent to destination personality, while self-congruence and destination personality each positively relate to the visit intentions of tourists. Conversely, one’s destination image does not predict self-congruence. In contributing to the literature at the intersection of royal and dark tourism, this underpins sustainability in tourist tourism, destination marketing, and consumer behaviour. The implications of such a study are found to fall in line with the United Nations SDGs, specifically Goal 8: Decent Work and Economic Growth, regarding the promotion of sustainable tourism, which brings in income and provides employment; and Goal 11: Sustainable Cities and Communities, due to the fostering of conservation and promotion at the cultural heritage sites.